KINERJA KEUANGAN DALAM MEMPREDIKSI FINANCIAL DISTRESS - Nurhidayah, Nurhidayah; Rizqiyah, Fitriyatur (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2017)
This study aims to determine the prediction of financial distress in the manufacturing industry sub-sector food and beverage listed on the Indonesia Stock Exchange. The research period is 2011-2015. In this study, using the indicator liquidity, profitability, inflation, and exchange rates. The study population includes all sub-sectors of food and beverages listed on the Indonesia Stock Exchange 2011-2015 period. The sample is determined by purposive sampling technique. Data analysis method used is logistic regression analysis. The results showed that the current ratio, return on investment and the net profit margin, and the inflation rate is the most significant variable in predicting financial distress, while the exchange rate is the only variable that was not significant in influencing financial distress.